Modularity in dance: Effects of expertise on the production and perception of full-body movements through the use of a Bayesian generative model based on temporal movement primitives - Leh, Liv Amalaswintha; Justus Liebig University Giessen (My University, 2026)
Dance can be viewed as a form of full-body art that has been practiced by humans for thousands of years in various social contexts. However, the relationship between the configuration of these expressive movements and the aesthetic qualities they elicit in observers is still unclear. According to current understanding, humans may be able to generate a variety of movement by relying on movement primitives: a pool of fundamental movement building blocks that can be flexibly combined to produce diverse movements. Years of sensorimotor experience might modulate these types of primitives, resulting in the motor skills observed in professional dancers today and their aesthetic performance. The main objective of this thesis was to enhance our understanding of how the aesthetic perception of dance movements relates to their modular composition. To this end, a generative model based on movement primitives was implemented, its viability as a tool for perceptual experiments was tested, and finally applied to the aesthetic evaluation of artificially generated dance movements. All in all, four experiments were conducted. The first experiment examined the temporal segmentation of dance sequences, as this is a necessary pre-processing step for the implemented model, showing that using simple kinematic features is a viable approach for segmenting dance sequences up to a certain degree of fluidity. The second experiment focused on the perceptual validation of the model for dance movements, as this had not yet been evaluated. The findings indicate that the model is perceptually valid and robust to a range of factors, although its validity may be limited when movement complexity reaches a certain level. The third experiment goes beyond methodological assessments to explore how the modular composition of dance movements relates to sensorimotor dance experience. The results suggest that sensorimotor dance experience is associated with a more movement primitives, but fewer temporal segments. Finally, the fourth experiment assessed the aesthetic perception of dance movements based on their composition. Interestingly, movements based on a greater number of primitives also received higher aesthetic evaluations, which contrasts with previous studies on the aesthetic perception of dance. An exception to this pattern was observed, suggesting an uncanny valley phenomenon for artificial full-body movements. Overall, this thesis addressed both methodological and conceptual aspects of dance movement production and perception within a modular framework, identifying limitations and offering directions for future research on the generation and appreciation of full-body artistic movement.